DIGITAL TRANSFORMATION IN HR MANAGEMENT: EMBRACING A NEW ERA OF DIVERSITY AND INCLUSION - Wellia Novita; Andre Ilyas; Andry Novrianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the impact of digital transformation on diversity and inclusion (D&I) within Human Resource (HR) practices, focusing on how AI and data-driven tools enhance recruitment, performance evaluation, and employee engagement. Through a qualitative case study of HR departments in Indonesia, key findings reveal that digital tools reduce biases in hiring and foster a more inclusive work environment. However, challenges such as algorithmic bias and depersonalization of employee experiences were also identified, indicating the need for a balanced approach. This study contributes to understanding the practical applications of digital transformation in D&I, offering recommendations for HR departments to conduct regular audits of AI tools and adopt hybrid models that integrate both digital and human-centered practices. Future research should expand on these findings by exploring diverse cultural contexts and the long-term effects of digital HR practices on inclusivity. This research underscores the importance of ethical AI use and provides valuable insights for creating inclusive, diverse workplaces.